2019
DOI: 10.1186/s12885-019-5558-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of M-CSF and VEGF in laboratory diagnostics and differentiation of selected histological types of cervical cancers

Abstract: Background The search of useful serum biomarkers for the early detection of cervical cancers has been of a high priority. The activation of Macrophage-Colony Stimulating Factor (M-CSF) and Vascular Endothelial Growth Factor (VEGF) is likely involved in the pathogenesis and spread of cancer. We compared the plasma levels of M-CSF and VEGF to the ones of commonly accepted tumor markers CA 125and SCC-Ag in three groups of patients: 1. the cervical cancer group (patients with either squamous cell carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…Macrophage colony-stimulating factor (M-CSF) is a hematopoietic growth factor that stimulates the proliferation and differentiation of Monocytes to macrophages. Experimental studies have shown that increased expression of M-CSF and its receptor leads to recruitment of tumor-associated macrophages (TAMs) in different types of cancers that also stimulate cancer cell proliferation and migration [5,47,48]. Consequently, M-CSF overexpression in plasma levels serves as useful predictor of carcinogenesis, and poor prognosis [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Macrophage colony-stimulating factor (M-CSF) is a hematopoietic growth factor that stimulates the proliferation and differentiation of Monocytes to macrophages. Experimental studies have shown that increased expression of M-CSF and its receptor leads to recruitment of tumor-associated macrophages (TAMs) in different types of cancers that also stimulate cancer cell proliferation and migration [5,47,48]. Consequently, M-CSF overexpression in plasma levels serves as useful predictor of carcinogenesis, and poor prognosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, four of the studies evaluating Vascular Endothelial Growth Factor (VEGF) assays included in our review recorded sensitivity, specificity, and AUC ranges of 56-83.5%, 74.6-96%, and 0.83-0.86, respectively, [5,[50][51][52], with 86% PPV and 82% NPV reported by Ławicki, et al [50]. Our review findings supports earlier suggestion by Sidorkiewicz et aland Cheng et al, of the diagnostic usefulness, and clinical applicability of VEGF assay in cervical, breast or endometrial cancer, particularly with regards to consistency in specificity and AUC across all studies; and the diagnostic correlation with other complementary assays such as M-CSF and SCC-Ag [5,51]. Members of Vascular Endothelial Growth Factor (VEGF) family comprising VEGF-A, −B, −C, −D, and placenta growth factor (PlGF) are dimeric glycoprotein measuring 34-42 kDa, and constitutes one of the most important signaling pathways associated with angiogenesis [75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum M-CSF appears to improve the diagnostic reliability of serum CA 125 alone [ 73 ]. • This biomarker expressed also in other cancers [ 74 ]. Bikunin Mediates suppression of tumor cell invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%